2018
DOI: 10.1038/s41598-018-33241-0
|View full text |Cite|
|
Sign up to set email alerts
|

First assessment of the comparative toxicity of ivermectin and moxidectin in adult dung beetles: Sub-lethal symptoms and pre-lethal consequences

Abstract: Among macrocyclic lactones (ML), ivermectin (IVM) and moxidectin (MOX) potentially affect all Ecdysozoan species, with dung beetles being particularly sensitive. The comparative effects of IVM and MOX on adult dung beetles were assessed for the first time to determine both the physiological sub-lethal symptoms and pre-lethal consequences. Inhibition of antennal response and ataxia were tested as two intuitive and ecologically relevant parameters by obtaining the lowest observed effect concentration (LOEC) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
18
0
3
Order By: Relevance
“…Noteworthy advances in this regard were derived from studies on the sensitivity of multiple species of dung flies to MLs (Blanckenhorn et al, 2013), which found that the toxicity of MLs varies considerably across the phylogenetic range of dung flies, and that sensitivity to MOX, though lower in potency, was correlated with sensitivity to IVM, suggesting that variations in either internal accumulation or target affinity are conserved among these arthropod species. A detailed study of the toxicity of MOX and IVM in juvenile and adult dung beetles ( Scarabaeus cicatricosus ) using multiple physiological and developmental assays found that MOX is 5–6 times less potent than IVM against these organisms (Verdú et al, 2018), a finding consistent with previous work. Based on threshold concentrations required for observable effects, this study also reported that fecal concentrations of MOX declined to sub-toxic levels more quickly than for IVM (2 vs. 4 weeks).…”
Section: Ecotoxicologysupporting
confidence: 86%
“…Noteworthy advances in this regard were derived from studies on the sensitivity of multiple species of dung flies to MLs (Blanckenhorn et al, 2013), which found that the toxicity of MLs varies considerably across the phylogenetic range of dung flies, and that sensitivity to MOX, though lower in potency, was correlated with sensitivity to IVM, suggesting that variations in either internal accumulation or target affinity are conserved among these arthropod species. A detailed study of the toxicity of MOX and IVM in juvenile and adult dung beetles ( Scarabaeus cicatricosus ) using multiple physiological and developmental assays found that MOX is 5–6 times less potent than IVM against these organisms (Verdú et al, 2018), a finding consistent with previous work. Based on threshold concentrations required for observable effects, this study also reported that fecal concentrations of MOX declined to sub-toxic levels more quickly than for IVM (2 vs. 4 weeks).…”
Section: Ecotoxicologysupporting
confidence: 86%
“…It is derived by chemical optimization of F-alpha or nemadectin (LL F-2924α), a fermentation product of the bacterium Streptomyces cyanogriseus ssp. noncyanogenus, through the addition of a methoxime moiety at carbon 23 [18]. Moxidectin differs from ivermectin (also a macrocyclic lactone but of the avermectin family) in the absence of a disaccharide attached to carbon 13, the presence of an olefinic side chain at carbon 25, and a methoxime moiety at carbon 23.…”
Section: Chemistrymentioning
confidence: 99%
“…Moxidectin differs from ivermectin (also a macrocyclic lactone but of the avermectin family) in the absence of a disaccharide attached to carbon 13, the presence of an olefinic side chain at carbon 25, and a methoxime moiety at carbon 23. The chemical structures of ivermectin and moxidectin are compared in [18].…”
Section: Chemistrymentioning
confidence: 99%
“…In soil, ivermectin shows a half-life degradation between 7 and 217 days, depending on the solar radiation [3]. Once on the environment, this drug has pre-lethal consequences for dung beetles [30] and for other dung-dwelling invertebrates [3]. If the drug is delivered orally in feeding stuff, as per common practice in game ungulate populations in Spain, soil contamination and thus the potential effects of ivermectin on other terrestrial fauna, and possibly food chain effects, could be expected not only through fecal contamination but through the drug preparation itself.…”
Section: Open Accessmentioning
confidence: 99%